Penerapan Metode Pembiasaan Dalam Menanamkan Nilai-Nilai Pendidikan Islam Pada Siswa Sekolah Dasar - Ilham Muhammad; Septiawan Septiawan (Prodi PGSD Unsultra, 2021)
This study aims to examine the implementation of Islamic education values through the habituation method among students in a public elementary school located in South Konawe Regency. This research employs a qualitative descriptive approach. The research informants consisted of the school principal, three teachers, and six students. Data were collected through interviews, observations, and documentation. The findings indicate that the application of the habituation method in instilling Islamic education values among students is quite effective. This method helps foster students’ character in practicing queue discipline, disposing of waste properly, greeting and being polite, praying before doing activities, demonstrating good behavior and morals, memorizing short surahs, and maintaining discipline in performing worship.